Skeletal muscle mass and kidney function among Chinese older adults: a cross-sectional study - Yu Li; Yan Yang; Jing Wang (Renal Failure)
Objectives To assess the association between kidney function and odds of having low skeletal muscle mass (LSMM) in Chinese adults on the basis of a community study.Data and methods In this cross-sectional study, we included 3726 Chinese older persons who participated in an ongoing prospective study, the China Health and Retirement Longitudinal Study(CHARLS). Fasting blood samples were collected in 2012 and analyzed for serum creatinine. Estimated glomerular filtration rate(eGFR) was computed using serum creatinine, gender, and age, according to the 2021 race-free Chronic Kidney Disease Epidemiology Collaboration equation (CKD-EPI). We classified the target population into three categories according to eGFR (normal eGFR;90mL/min/1.73m2, mildly-impaired eGFR;60 to < 90 mL/min/1.73 m2, moderate to severve impaired eGFR;<60 mL/min/1.73 m2). BMI-adjusted muscle mass was used to measure skeletal muscle mass. The association between eGFR(per interquartile range(IQR) increment) and the risk of low skeletal muscle mass was assessed using logistic regression model.Results Worsening renal function was associated with being high risk for LSMM after adjusting for potential confounders:the odds ratios (ORs) 95% confidence intervals (CIs) were 0.76 (95% CI = 0.63 − 0.88) for male, and [0.71, (0.61-0.82)]in female, p < 0.001. Specifically, male participants with mildly renal impairment were more prone to develop LSMM (multiadjusted OR, 1.43, 95% CI(0.92 to 2.09), p = 0.1) than femal(multiadjusted OR, 1.32, 95% CI(0.85 to 2.00), p = 0.2), the gender difference was not significant in severe renal dysfunction. However, there was a non-linear relationship between eGFR(per IQR increment) and risk of LSMM(eGFR/IQR =5.42, knot = 4 OR =1, p for non-linear <0.001).Conclusions Lower levels of eGFR had a high likelihood of being high risk for LSMM. Older male patients with mildly renal insufficiency are more likely to experience a decrease in skeletal muscle mass compared to female.